New Mutations Involved in Colistin Resistance in Acinetobacter baumannii - Bingbing Sun (American Society for Microbiology, 2020)
ABSTRACT Colistin is used as the “last resort” to treat infections caused by multidrug-resistant Acinetobacter baumannii, which is at the top of the World Health Organization’s list of the most dangerous bacterial species that threaten human health. Unfortunately, colistin resistance has emerged in A. baumannii. To broaden the study of the resistance mechanism of colistin in A. baumannii, we obtained colistin-resistant mutants via two methods: (i) screening and isolation from a mariner-based A. baumannii ATCC 19606 transposon mutant library; (ii) selection from challenge of ATCC 19606 with successively increasing concentrations of colistin. A total of 41 mutants with colistin MIC of 4 μg/ml to 64 μg/ml were obtained by transposon mutant library screening. Five highly resistant mutants with colistin MICs ranging from 256 μg/ml to 512 μg/ml were selected from successive colistin challenges. Genotypic complementation and remodeling of the transposon mutants revealed that the genes inactivated by the transposon insertion were not responsible for resistance. Whole-genome sequence analysis of the colistin-resistant strains revealed that the main causes of the resistance to colistin were mutations in the pmrA-pmrB genes, including pmrAP102R, pmrBP233S, and pmrBT235N and the novel alleles pmrAI13M and pmrBQ270P. Interestingly, we found that miaAI221V mutation of A. baumannii strain ATCC 19606 (pmrAP102R) resulted in 4-fold increases in the colistin MIC, which rose from 32 μg/ml to 128 μg/ml. But miaAI221V itself had little effect on the colistin susceptibility of ATCC 19606. These data broaden knowledge of the scope of chromosomally encoded mechanisms of resistance to colistin. IMPORTANCE Acinetobacter baumannii is an important Gram-negative opportunistic pathogen commonly infecting critically ill patients. It possesses a remarkable ability to survive in the hospital environment and acquires resistance determinants corresponding to a wide range of antibacterial agents. Given that the current treatment options for multidrug resistant A. baumannii are extremely limited, colistin administration has become the treatment of last resort. However, colistin-resistant A. baumannii strains have recently been reported. The mechanism of resistance to colistin in A. baumannii has rarely been reported. Here, we found two novel mutations in pmrA (I13M) and pmrB (Q270P) that caused colistin resistance. It is also first reported here that the presence of miaA with a I221V mutation enhanced the colistin resistance of pmrAP102R.